Noise Analysis of Trans-impedance Amplifier (TIA) in Variety Op Amp for use in Visible Light Communication (VLC) System - Syifaul Fuada; Angga Pratama Putra; Yulian Aska; Trio Adiono (International Journal of Electrical and Computer Engineering (IJECE), 2018)
VLC is a complex system with lots of challenges in its implementation. One of its problems is noise that originated from internal and external sources (sunlight, artificial light, etc). Internal noise is originated from active components of analog front-end (AFE) circuit, which will be discussed in this paper, especially on the trans-impedance amplifier (TIA) domain. The noise characteristics of AFE circuit in VLC system has been analyzed using the variety of available commercial Op Amp and different types of the photodiode (Si, Si-PIN, Si APD). The approach of this research is based on analytical calculus and simulation using MATLAB®. The results of this research show that the main factor that affecting the noise is en, the feedback resistor (Rf), and junction capacitor in the photodiode (Cj). Besides that, the design concept of multi channel TIA (8 channel) using IC Op Amp, with consideration of pin number of each Op Amp, supply needs, the initial value of Rf, converter to 8-DIP and feedback capacitor (Cf) channel, also discussed in this paper.